Type 2 Diabetes Mellitus and Demodex folliculorum Infestation: A Cross-Sectional Study in Peruvian Patients - Bendezu-Quispe, Guido (2022)
“Background: Demodex folliculorum is a mite that causes human demodicosis, which is characterized by producing lesions on the face, and its infestation could be associated with factors that alter the immune response, including Type 2 Diabetes (T2D). This study aimed to evaluate the relationship between T2D and D. folliculorum infestation in patients attended at a hospital in Peru in 2021. Methods: A cross-sectional study enrolling patients who were classified according to the presence (n = 100) and absence (n = 100) of T2D was conducted. Information was obtained on age, sex, domestic animal husbandry, and symptoms and signs associated with demodicosis. Demodicosis was determined to be present when counts of D. folliculorum greater than five mites per cm2 were found in superficial facial skin biopsies. Results: A frequency of demodicosis in 76 and 35 patients with and without T2D, respectively, was observed. In the multivariate analysis adjusted for confounders age, sex, and domestic animal husbandry, T2D was found to be associated with D. folliculorum infestation (PR: 2.13; 95% CI95: 1.42-3.19). Conclusions: T2D was associated with D. folliculorum infestation. In this sense, it is important to strengthen surveillance to identify of D. folliculorum infestation in people with T2D.“